PENGARUH MODEL PROJECT-BASED LEARNING BERBANTUAN MEDIA REALIA TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - andika, Rian; Luthvi Azizah, Alif; Dian Putra, Agung; Khairani, Fadhilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the project-based learning model assisted by realia media on the learning outcomes of fifth-grade students in IPAS subjects at SD Negeri 4 Metro Timur. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design involving an experimental class and a control class. Data were collected through pretest and posttest instruments and analyzed using simple linear regression. The results showed that the average posttest score of the experimental class was higher than the control class. The hypothesis test also indicated a significance value of 0.000 < 0.05, meaning that Ha was accepted and H0 was rejected. Therefore, it can be concluded that the implementation of the project-based learning model assisted by realia media had a significant effect on students’ learning outcomes in IPAS subjects.